Collaborative Learning in Graphic Design Education. - Rohidi, Tjetjep Rohendi; Ibrahim, Md. Nasir; Yusoff, Syed Osman Syed (International Journal of the Humanities, 2009)
This paper relates to the practice of collaborative learning in graphic design education. The aim of the research is to compare the process of creation between individuals, individual assisted, and team effort in the learning process. This study employed an action research to study collaborative learning among 12 students majoring in Advertising in Universiti Pendidikan Sultan Idris. The findings of this study revealed that the collaborative assignments displayed a more unified engagement by all members and the difference between individual and collaborative production and learning process. The individual assignment exercise displayed a rigid and unimaginative approach to the task, while the collaborative approach expressed more open and flexible attitude among the individuals. The final product of the collaborative work was better than the individual effort because of a number of interventions.